Phytoremediation of Phosphate content in liquid laundry waste by using Echinodorus paleafolius and Equisetum hyemale used as biology learning resource - Ayu Maharani Siswandari; Iin Hindun; Sukarsono Sukarsono (JPBI (Jurnal Pendidikan Biologi Indonesia), 2016)
Laundry liquid waste is the remain water of clothes washing process which causes toxic effects to the biotic area in the water in case of the liquid waste without proper processing. Phytoremediation is a system which is conducted by plants to break a contaminant compound into the non-hazard materials. This research aimed to analyze the mechanism to reduce phosphate content in laundry liquid waste by through phytoremediation process which had been done by using Echinodorus paleafolius and Equisetum hyemale. The research is quantitative descriptive in which the data analysis method was descriptive. The research was conducted in 17 May to 10 June 2016 in the Laboratory of Water Quality of Perum Jasa Tirta Jl. Surabaya No. 2A Malang. The research results showed that the phosphate content in laundry liquid waste exceed of threshold limit value of liquid waste standard which has been issued as PP No. 82 Year 2001. Therefore, this over limit of phosphate content is hazardous to be released to the environment. Echinodorus paleafolius is able to reduce the phosphate content as much as 3.451 mg within the high-density-phosphate waste and as much as 2.271 mg within the lower one. However Equisetum hyemale could not be used to reduce the phosphate content even though it could reduce acidity degree (pH) as much as 3.7 unit within this liquid waste through phytoremediation process. The implementation of the research results was the contextual handout which is completed with colored pictures.